PENGEMBANGAN MODUL BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MATERI PENERAPAN ALJABAR DALAM MENYELESAIKAN MASALAH ARITMATIKA SOSIAL PADA PEMBELAJARAN MATEMATIKA KELAS VII SMPN 16 PADANG - Julian, Sri Thirteen (STKIP PGRI Sumbar, 2014)
This developmental research was based on the teaching materials such astextbooks used by students could not construct the way of students thingking,independent learning, and the students could not relate the learning materialswhich have been studied into the daily life. The attemp done to solve the problemsis by developing teaching materials in the form of a module-based of ContextualTeaching and Learning (CTL). This research is aimed to determine the validityand to find out the practicality of module-based CTL in the materials about theimplementation of algebra in solving the social arithmetic problems. This type ofresearch was developmental research by using 4-D model. It was done until thephase of development. According to validators, it was found that the result of thevalidity was valid. The result of the practicality of the module from the studentsand teachers expressed that the module was very practical.